Insight into synthesis and characterisation of Ga0.9Fe2.1O4 superparamagnetic NPs for biomedical applications - Amalia Mesaros; Alba Garzón; Mircea Nasui; Rares Bortnic; Bogdan Vasile; Otilia Vasile; Florin Iordache; Cristian Leostean; Lelia Ciontea; Josep Ros; Ovidiu Pana (Scientific Reports, 2023)
Abstract A Ga3+-substituted spinel magnetite nanoparticles (NPs) with the formula Ga0.9Fe2.1O4 were synthesized using both the one-pot solvothermal decomposition method (TD) and the microwave-assisted heating method (MW). Stable colloidal solutions were obtained by using triethylene glycol, which served as a NPs stabilizer and as a reaction medium in both methods. A narrow size distribution of NPs, below 10 nm, was achieved through selected nucleation and growth. The composition, structure, morphology, and magnetic properties of the NPs were investigated using FTIR spectroscopy, thermal analysis (TA), X-ray diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and magnetic measurements. NPs with the expected spinel structure were obtained in the case of the TD method, while the MW method produced, additionally, an important amount of gallium suboxide. The NPs, especially those prepared by TD, have superparamagnetic behavior with 2.02 μB/f.u. at 300 K and 3.06 μB/f.u. at 4.2 K. For the MW sample these values are 0.5 μB/f.u. and 0.6 μB/f.u. at 300 K and 4.2 K, respectively. The MW prepared sample contains a secondary phase and very small NPs which affects both the dimensional distribution and the magnetic behavior of NPs. The NPs were tested in vitro on amniotic mesenchymal stem cells. It was shown that the cellular metabolism is active in the presence of Ga0.9Fe2.1O4 NPs and preserves an active biocompatible cytoskeleton.